Investigation of physical and mechanical properties of peat - V. Kulikov, Aleksandr; V. Vorontsov, Vyacheslav; N. Shuvaev, Anatolii (International Journal of Engineering and Technology, 2018)
The article describes results of laboratory tests of weak water-saturated soils (remote from day surface) in stress-strain state under influence of compression with double-sided filtration of pore’s water. The experimental device with console-lever system of load transfer and potential of double-sided filtration was made for current research. The compression specification was controlled with the strain gauge sensor element of general pressure (i.e. the load cell).The deformation in sample were measured with the motion detecting transducer that based on indicating gage. The excessive pore pressure was measured with strain gauge sensor elements and digital manometer. Also the plots of compression deformation against pressure and changes of excessive pore pressure during the time on different load degrees were drawn. Although, authors made the new experimental device for research of the water saturated peat mechanics properties with excessive pore pressure.